1995
DOI: 10.1074/jbc.270.15.8829
|View full text |Cite
|
Sign up to set email alerts
|

Mutually Exclusive Interactions between Factors Binding to Adjacent Sp1 and AT-rich Elements Regulate Gastrin Gene Transcription in Insulinoma Cells

Abstract: The gastrin gene is transiently expressed in fetal pancreatic islets during islet neogenesis but then switched off after birth when islet cells become fully differentiated. Previous studies identified a cis-regulatory sequence between -109 and -75 in the human gastrin promoter which binds islet cell-specific activators and a nonspecific repressor and thus may act as a molecular switch. The present study identified another cis-regulatory sequence (-163ACACTAAATGAAAGGGCGGGGCAG-140) which bound two islet nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
5
13
0
Order By: Relevance
“…RasN17 suppressed both basal and ITF-induced hpS2-driven reporter activity. Suppression of Ras signaling by RasN17 was confirmed by the ability to block EGF-induced trans-activation of the human gastrin promoter (Figure 5), previously reported to be Ras dependent (30).Consistent with this data, cotransfection of wild-type c-Ha-Ras was able to strongly induce both basal and ITFinduced pS2 and SP reporter activity (data not shown).…”
Section: Figuresupporting
confidence: 76%
See 2 more Smart Citations
“…RasN17 suppressed both basal and ITF-induced hpS2-driven reporter activity. Suppression of Ras signaling by RasN17 was confirmed by the ability to block EGF-induced trans-activation of the human gastrin promoter (Figure 5), previously reported to be Ras dependent (30).Consistent with this data, cotransfection of wild-type c-Ha-Ras was able to strongly induce both basal and ITFinduced pS2 and SP reporter activity (data not shown).…”
Section: Figuresupporting
confidence: 76%
“…The kinase-deficient EGF receptor (EGF-R) expression plasmid pRK5-HER653 (29) was a gift from M. Korc (University of California-Irvine, Irvine, California, USA). The human gastrin promoter fused to luciferase, containing Ras and EGF response elements (30), was a gift from D. Chung (Massachusetts General Hospital/ Harvard Medical School). The Renilla luciferase reporter vector pRL-TK was obtained from Promega Corp. Purified recombinant human SP and ITF, produced in yeast, have been described previously (9,31).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies based on transient transfections of human gastrin promoter constructs in cultured rat islet cell lines identified an islet-cell-specific enhancer (7)(8)(9). This enhancer sequence in the human gastrin promoter was located within 200 bp of the transcriptional initiation site.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins-Additional EMSAs were performed utilizing EGTA to identify which factors may require Zn 2ϩ for DNA binding (31). These data revealed that complexes a and b, and to a lesser extent complex c, were attenuated (Fig.…”
Section: Zn 2ϩ Chelation and Ultraviolet Light-induced Cross-linking mentioning
confidence: 99%